Investigation into Intracellular Energy and Mechanism of Weak Electromagnetic Waves on the Whole Body by IR-Spectroscopia is a New Trend in Medicine - Dodtievich, Bitsoev Vladimir (Highlights on Medicine and Medical Research Vol. 3, 2021)
The present paper is devoted to the investigation of the important issues of modern medicine related to the improvement of early disease detection to make it safe and accessible to everyone who needs assistant and to provide treatments for diseases at the supramolecular level. Relying on experiments, we have a good reason to review the impact of faint electromagnetic waves on the whole organism. In this regard, we have identified the major challenges of clinical physiotherapy and created the classification scheme for physical factors based on new principles which may contribute to the development of physiotherapy theory.